Reactions between minerals and aqueous solutions - Ruiz-Agudo, E.; Putnis, Christine; Rodríguez-Navarro, C. (MINERALOGICAL SOCIETY GREAT BRITAIN & IRELAND, 2017)
© 2017 the European Mineralogical Union and the Mineralogical Society of Great Britain & Ireland. Kinetics of reactions between minerals and solutions govern a wide range of natural and technological processes including weathering and soil formation, nutrient availability, biomineralization, acid mine-drainage, the fate of contaminants, or nuclear waste disposal. Theoretical and experimental studies performed in recent decades have changed our understanding of the mechanisms of mineral-solution reactions significantly. This chapter reviews recent results and advances in terms of non-classical mineral-growth processes (pre-nucleation clusters, liquid and amorphous precursor phases or the occurrence and participation of nanoclusters as building blocks in the growth process) as well as other mineral-solution equilibration processes occurring by interface-coupled dissolution-precipitation reactions, which lead to replacement of the original mineral assemblage.